Dimensi Pragma-Dialektis Fatwa - Makyun Subuki (Universitas Islam Negeri Jakarta, 2015)
This study aimed to describe Dimension of Pragma-Dialectics Fatwa, especially in deciding the first month of Hijriah, such as Ramadhan, Syawal and Zulhijjah. The fatwa came from three Islamic religion institutions in Indonesia including Muhammadiyah, Nahdlatul Ulama and Indonesian Council of Ulama. In this case, any fatwa related to the issue is assumed mutual dialogue and trying to find a way out of dissent.DOI: 10.15408/ajis.v15i2.2856